2014
DOI: 10.1063/1.4876878
|View full text |Cite
|
Sign up to set email alerts
|

Development of multifunctional carbon fiber reinforced composites (CFRCs) - Manufacturing process

Abstract: This work describes a successful attempt toward the development of CFRCs based on nanofilled epoxy resins. The epoxy matrix was prepared by mixing a tetrafunctional epoxy precursor with a reactive diluent which allows to reduce the viscosity of the initial epoxy precursor and facilitate the nanofiller dispersion step. As nanofiller, multiwall carbon nanotubes (MWCNTs) were embedded in the epoxy matrix with the aim of improving the electrical properties of the resin used to manufacture CFRCs. Panels were manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…CFRCs were manufactured by a non-usual resin film infusion (RFI) process, described in previous papers [20,39]. A laminate configuration (0/90) n was used for the purpose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CFRCs were manufactured by a non-usual resin film infusion (RFI) process, described in previous papers [20,39]. A laminate configuration (0/90) n was used for the purpose.…”
Section: Methodsmentioning
confidence: 99%
“…Aeronautical epoxy resins and their hardener agents containing phosphorus have been synthesized and used to prepare epoxy formulations and CFRCs [1,3,37,38]. Recently, CFRCs have been manufactured adopting a modified resin film infusion (RFI) process (named “bulk infusion”) [20,39,40]. In particular, the difference in the electrical performance of carbon fiber-reinforced composites (CFRCs) made with two different resin film infusion (RFI) manufacturing techniques has been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…This particular epoxy formulation has proven to be very effective for improving nanofiller dispersion due to a decrease in the viscosity [19e22] and, in addition, it has been found to reduce the moisture content which is a very critical characteristic for aeronautic materials [19,23]. Furthermore, in order to minimize the filtration effects [24,25], the traditional liquid infusion process has been modified as described in the sequel.…”
Section: Introductionmentioning
confidence: 99%
“…The non-traditional liquid infusion technique for the preparation of the carbon fiber reinforced polymer (CFRP) panels has already been used by Guadagno et al [49,50] to obtain CFRP panels impregnated using resin with 0.5 wt% CNTs and turned out to be successful in reducing filtration problems and the formation of big CNTs agglomerates. The authors demonstrated that with this unconventional technique, compared to the traditional resin infusion process, significant improvements of the electrical conductivity were achieved, equal respectively to about 72% for the in-plane and 120% for the out-plane.…”
Section: Methodsmentioning
confidence: 99%